A Clinicopathological Analysis of 120 Cases of Prostate Biopsies and Their Correlation with Prostate Specific Antigen levels - Issac, Anu Sumi; Varughese, Ashley Ann; Raghuveer, C V; P, Asha S; K, Preetha; Majeed, N Abdul; Rajan, Junu (Annals of Pathology and Laboratory Medicine, 2018)
Interpretation of prostate lesions in TURP and needle biopsies have always been a challenge due to their varied presentation. PSA, produced by epithelial cells of all types of prostatic tissue, is the key factor for screening and detection of prostate cancer. The present study aimed to analyze the histopathological changes of prostate and correlate them with PSA levels. Methods: One hundred and twenty cases of prostate lesions were obtained in two years. H&E stained sections were examined and a histopathological diagnosis was given. Result: Out of the 120 cases, 92 (76.7%) were Benign Prostatic Hyperplasia (BPH), 9 (7.5%) were Prostatic Intraepithelial Neoplasia (PIN) and 19 (15.8%) were Prostate Carcinoma (PCa). All three lesions presented predominantly with obstructive lower urinary tract symptoms. In the BPH group, mean age was 66 years and mean PSA of 7.21ng/mL. In the PIN group, majority were low grade PIN (77.8%), mean age of 66.56 years and mean PSA 38.23ng/mL. The highest PSA obtained in this study was 199ng/mL in a case of low grade PIN. In the Prostate carcinoma group, mean age was 66 years, mean PSA 63.8 ng/mL, majority were conventional adenocarcinomas (94.7 %). Most of the carcinomas had a Gleason sum < 6 and were well differentiated tumours (52.6%). Conclusion: All three groups had a common mean age of presentation and serum PSA levels were not always conclusive of the concerned pathology. Therefore, prostate lesions should be thoroughly evaluated by histopathology keeping in mind their neoplastic potential.